VEGETASI LANSKAP JALAN SEBAGAI PEREDUKSI ALIRAN ANGIN DI KOTA KUPANG - Roosna Maryani Octaviana Adjam; Emi Renoat (http://arl.faperta.ipb.ac.id/, 2017)
Kupang City in East Nusa Tenggara is one of the coastal area in Indonesia that has the high speed of wind flows. Leaving the rainy season in May and entering the dry season from June to October each year brings the peak wind season from the northwest. It may reach 28-30 Knots grade (Meteorology, Climatology, and Geophysics Climatology Station of Lasiana, Kupang, 2014). The wind flow has disturbed the safety of road users in the city. The study aim to determine the amount and the impact of wind speed that occurs at three locations of roads, comparing some road vegetations which the best and the worst in solving the wind flow problem, and to develop the road planting plan to reduce the wind flow of road landscape in Kupang. The study was conducted on three roads with vegetation plot include Frans Seda, Piet Tallo and Herman Johanes roads. Wind flow measurements made on each side of the road that exposed to the wind. The study was conducted in May until December 2015. The most effective spot in reducing wind flow is at penghijauan spot with the great number and kind of vegetations, tree canopy and tree rapidity in the area. The worst spot for wind reducer is at Liliba spot and Pertamina spot in Herman Johanes road. The result is supporting by 4 factorial designs which showed that the roads have low rapidity of plants, the sort and height of vegetations which are below 5 meters at the road.